Education for all in India - Mehta, Arun C. (2005)
[Dt.:] Arun C. Mehta ist Fellow am National Institute of Educational Planning and Administration (NIEPA). Auf seiner privaten Homepage informiert er über den Stand und die Entwicklung des Bildungs- und Schulwesens in Indien. Frei zugänglich sind eine Vielzahl von Daten und Datenanalysen zum Thema Bildung in Indien. Zudem informiert Arun C. Mehta über seine eigenen Forschungsprojekte und Veröffentlichungen. - [Engl.:] Arun C. Mehta is Research Fellow at the National Institute of Educational Planning and Administration (NIEPA). On his personal hompage he makes available informations about the historical and contemporary development of the Indian educational system. The website contains data, samples and analyses of education in India. There are also informations about the author, his research interests and publications.